1977
DOI: 10.1071/ar9770355
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration and leaf water potentials of wheat in relation to changing soil water potential

Abstract: Changes in the transpiration rate of wheat in drying soils were followed in experiments in which plants were grown in two small weighable lysimeters in a glasshouse. Hourly measurements of soil water potential (Ψs) were made at three depths in each lysimeter. The water potential of flag leaves was measured with a pressure chamber, and stomatal resistance with a pressure drop porometer. Data on root densities and distribution were also obtained. Transpiration rates fell below estimated potential levels when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The relationship between \jr t and E was markedly non-linear. Such non-linearity has been observed by many workers (Jones, 1978;Seaton, Landsberg & Sedgley, 1977;Hailey et al 1973). Landsberg & Fowkes (1978) have shown that non-linearity can occur because of variation in i/r, through the profile.…”
Section: Discussionmentioning
confidence: 65%
“…The relationship between \jr t and E was markedly non-linear. Such non-linearity has been observed by many workers (Jones, 1978;Seaton, Landsberg & Sedgley, 1977;Hailey et al 1973). Landsberg & Fowkes (1978) have shown that non-linearity can occur because of variation in i/r, through the profile.…”
Section: Discussionmentioning
confidence: 65%
“…The root radius was 0.072 (_+0.014) mm as determined from microscopy of 8 field grown barley root samples in 0.1 m deep layers from 0-0.4 m depth. In order to avoid interference from few thick main roots (Seaton et al, 1977) only the radii of laterals were determined. Within each sample 20 measurements of root radius were undertaken.…”
Section: Crop Parameters Measurements and Climatic Conditions Used Imentioning
confidence: 99%
“…Thick lines represent cases where transpiration was thought to be of minimal importance. Individual curves are: (M), 5 cm layer of 50-60% sand covered by little vegetation (Marsh et al, 1981); (DA), 5 cm layer of sandy loam covered by ryegrass (Davies and Allen, 1973); (R), 1.5 m layer of sandy loam, vegetation recently burned (Rouse et al, 1977); (D), 1 or 2 cm layer of soil, vegetation recently burned (Barton, 1979); (W), 5 cm layer of soil covered by dry rangeland grass (Williams et al, 1978); (MN), lo-20 cm layer of heavy clay covered by shallow rooted grass (Mukammal and Neuman, 1977); (BD), 25 cm layer of sandy loam with soybean crop (Bailey and Davies, 1981); (SC), 37 cm layer of sandy clay loam with wheat crop (Seaton er al., 1977); (S), 37 cm layer of sandy loam with wheat crop (Seaton et al, 1977).…”
Section: Direct Evaporationmentioning
confidence: 99%